1996
DOI: 10.1097/00006454-199611000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Histoplasmosis in Children: The Role of Itraconazole Therapy

Abstract: The results of this study indicate that itraconazole is effective for treatment of disseminated childhood histoplasmosis. More studies should be performed to determine the most appropriate dosage and the optimal duration of itraconazole treatment in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 13 publications
1
12
0
4
Order By: Relevance
“…Los Doctores Dodd y Tompkins en 1934, realizan por primera vez el diagnóstico en un niño. 3 Son pocos los casos de la forma diseminada en pacientes inmunocompetentes reportados hasta el momento en Colombia [6][7][8] . En los últimos años la incidencia en todos los grupos de edad viene en aumento, gracias a enfermedades que cursan con inmunocompromiso (asociado principalmente a infección por el virus de inmunodeficiencia humana -VIH) 3,10,11 o al uso de citotóxicos e inmunosupresores, especialmente micofenolato [11][12][13] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los Doctores Dodd y Tompkins en 1934, realizan por primera vez el diagnóstico en un niño. 3 Son pocos los casos de la forma diseminada en pacientes inmunocompetentes reportados hasta el momento en Colombia [6][7][8] . En los últimos años la incidencia en todos los grupos de edad viene en aumento, gracias a enfermedades que cursan con inmunocompromiso (asociado principalmente a infección por el virus de inmunodeficiencia humana -VIH) 3,10,11 o al uso de citotóxicos e inmunosupresores, especialmente micofenolato [11][12][13] .…”
Section: Discussionunclassified
“…4,5 Pocos casos han sido descritos en Colombia en la población pediátrica y menos aún en inmunocompetentes. [6][7][8] Se describe el caso de un niño con diagnóstico de histoplasmosis aguda diseminada con importante compromiso respiratorio.…”
Section: Introductionunclassified
“…capsulatum and Histoplasma capsulatum var. duboisii that cause disease in humans 2 The disease is classified into acute pulmonary histoplasmosis (normal host), disseminated histoplasmosis (immune defect) and chronic pulmonary histoplasmosis (structural defect) 3,4,5 . The acute histoplasmosis is usually asymptomatic, occasionally symptomatic but complications are rare 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The time course of the infection in these patients is measured in months, and the disease is uniformly fatal if not treated 4 . We report a case of disseminated histoplasmosis in a 13-year-old girl that mimicked a number of clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have found evidence supporting the possibility that airborne secondary metabolites produced by fungi, i.e., mycotoxins, and (1--3)-P-Dglucans, present in the cell wall of most filamentous fungi, may contribute to respiratory symptoms (6)(7)(8)(9). Opportunistic fungal infections are rare in children but may occur in the immunocompromised (10)(11)(12)(13).…”
mentioning
confidence: 99%